Let's break down the expression you provided step by step to verify it.
You are starting with the expression:
\[
\frac{7^{250}}{7^{-60}}
\]
Using the property of exponents \(\frac{a^m}{a^n} = a^{m-n}\), we can simplify it:
\[
7^{250 - (-60)} = 7^{250 + 60} = 7^{310}
\]
Now, let's also look at the second part of your calculations, which appears to be a separate expression:
\[
\frac{5^{182}}{5^{-60}}
\]
Using the same property of exponents:
\[
5^{182 - (-60)} = 5^{182 + 60} = 5^{242}
\]
So, your final answer of \(5^{242}\) from the second expression is correct.
Each expression simplifies individually, with \(7^{310}\) and \(5^{242}\) being their respective results. But you should ensure you are working with the correct terms as you combine or analyze different problems.
To summarize:
- \(\frac{7^{250}}{7^{-60}} = 7^{310}\)
- \(\frac{5^{182}}{5^{-60}} = 5^{242}\)
Both steps are correct for the respective expressions.